2014
DOI: 10.1159/000369788
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Levofloxacin- and Moxifloxacin-Based Triple Therapies with Standard Treatment in Eradication of Helicobacter Pylori as First-Line Therapy

Abstract: Aim: It is recommended that treatments that include clarithromycin should be avoided in eradication of Helicobacter pylori (HP) in cases where clarithromycin resistance is higher than 20%. We aimed to compare levofloxacin- and moxifloxacin-based triple therapies with standard treatment and with each other in eradication of helicobacter pylori as first-line therapy. Materials and Methods: Patients were randomized prospectively as three groups. There were 102 patients in the levofloxacin group, 101 patients in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…According to a multiregion prospective 7-year study by Liu et al[ 46 ], the prevalence of H. pylori after moxifloxacin treatment was 17.2%. Resistance to moxifloxacin was reported to be similar to that of levofloxacin, ranging from 14.9% to 20.0% in Turkey[ 29 ]. The increasing antibiotic resistance rate makes the eradication of H. pylori more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…According to a multiregion prospective 7-year study by Liu et al[ 46 ], the prevalence of H. pylori after moxifloxacin treatment was 17.2%. Resistance to moxifloxacin was reported to be similar to that of levofloxacin, ranging from 14.9% to 20.0% in Turkey[ 29 ]. The increasing antibiotic resistance rate makes the eradication of H. pylori more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Two other original studies also compared fluoroquinolone‐based triple therapy to standard triple therapy. A study from Turkey noted that the per‐protocol (PP) eradication rate was 92% in a levofloxacin triple therapy group, 92% in a moxifloxacin triple therapy group, and 82% in a clarithromycin triple therapy group, a statistically significant difference for the combined fluoroquinolone‐containing groups over clarithromycin . A study from Taiwan also showed a clear benefit for levofloxacin‐based 7‐day triple therapy compared to clarithromycin‐based treatment (78 vs 58%) .…”
Section: Fluoroquinolonesmentioning
confidence: 99%
“…The H. pylori eradication rate of standard triple therapy has been shown to be low in Turkey. The eradication rate of this regimen was 63.6% in the study of Avşar et al, 57% in the study of Polat et al and 82.4% in the study of Rakici et al [7][8][9]. In the study of Rakici et al, eradication of H. pylori was assessed by stool antigen testing, which may lead to false negative results due to standardization issues [10].…”
Section: Resultsmentioning
confidence: 99%